Language Policy Challenges in Multi-Ethnic Malaysia - Gill, Saran Kaur.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Set in Malaysia, this book encompasses language and cultural policy challenges that many other multi-ethnic nations currently have to address. The people of Malaysia constitute a diverse ethnic, linguistic and cultural population, and one of the continuing challenges is the development and establishment of the Malaysian people$1 (Bs ethnic, national and global cultural identities. This challenge is evident in the journey of language and cultural policy from the post-independence period to the 21st century; a period of over 50 years. The book highlights political, socio-cultural, economic and knowledge economy factors as they impact on decisions made by the government with regard to language policy in the various educational systems. It examines decisions made on the selection of the national language, the medium of instruction in educational systems, the varying changes in language policy for the field of science and technology and the maintenance and sustenance of minority languages.s
Foreword -- Preface -- Acknowledgement -- 1: Introducing the situational context, macro-sociolinguistics and key elements of language planning and policy in Malaysia -- 2: Language, nation-building and identity formation in a multi-ethnic society -- 3: The role of language education during colonial rule and post-independence period -- 4: Drastic change in the medium of instruction: From Bahasa Malaysia to English -- 5: The re-reversal from English to Bahasa Malaysia -- 6: The Impact of the change in medium of instruction in Malaysia on the Chinese community and mother-tongue education -- 7: The revival of a minority language in Malaysia: The dynamics between national linguistic ideology and ethnic linguistic identity -- 8: Conclusion: The road ahead for Malaysia: Balancing ethnic, national and international identities -- References.
Keywords: Education; Applied linguistics; Language and languages; Education; Educational Policy and Politics; Applied Linguistics; Language Education